Organ Preference of Cancer Metastasis and Metastasis-Related Cell Adhesion Molecules Including Carbohydrates - Kawaguchi, Takanori (Cardiovascular & Haematological Disorders - Drug Targets, 2015)
This review starts on one of our special interests, the organ preference of metastasis. We examined data on 1,117 autopsy cases and found that the organ distribution of metastasis of cancers of the lung, pancreas, stomach, colon, rectum, uterine cervix, liver, bile duct, and esophagus involved the lung, liver, adrenal gland, bone/bone marrow, lymph node, and pleura/peritoneum. Cancers of the kidney, thyroid, ovary, choriocarcinoma, and breast, however, manifested different metastatic patterns. The distribution of leukemia and lymphoma metastases was quite different from that of epithelial cancers. On the basis of experimental studies, we believe that the anatomical-mechanical hypothesis should be replaced by the microinjury hypothesis, which suggests that tissue microinjury induced by temporal tumor cell embolization is crucial for successful metastasis. This hypothesis may actually reflect the so-called inflammatory oncotaxis concept. To clarify the mechanisms underlying metastasis, we developed an experimental model system of a rat hepatoma AH7974 that embraced substrate adhesiveness. This model did not prove a relationship between substrateadhesion potential and metastatic lung-colonizing potential of tumor cells, but metastatic potential was correlated with the expression of the laminin carbohydrate that was recognized by Griffonia (Bandeiraea) simplicifolia isolectin G4. Therefore, we investigated the relationship between carbohydrate expression profiles and metastasis and prognosis. We indeed found an intimate relationship between the carbohydrate expression of cancer cells and the progression of malignant tumors, organ preference of metastasis, metastatic potential of tumor cells, and prognosis of patients.
Keywords: Tn antigen